An Analysis on Structural Ambiguity’s Patterns of The Most Watched News Headlines in BBC News - Diah Supatmiwati; Alan Cahya Saputra; Erwin Suhendra (Humanitatis : Journal of Language and Literature, 2022)
News is a particular content of media talk that has pulled in extraordinary intrigued. This think about picks up knowledge into how language structure shapes the representation of data in news stories. This research is a qualitative research on pattern of ambiguous headlines entitled “An Analysis on Structural Ambiguity’s Patterns Found in The Most Watched News Headlines in BBC NEWS”. The aim of this research is to find the pattern of structural ambiguity of the most watched news in BBC News headlines. Collectingdata inquires library data collection method (reading and note-taking technique). In this research, the researcher distinguishes the structural patterns using the syntactic theory of constituency grammar by Jurafsky (2014). The result of this research is seven of eight data which are data 1, data 2, data 4, data 5, data 6, data 7, and data 8 were ambiguous because of the order of the Preposition Phrase. In line with it, one of eight data which is data 3 was ambiguous because of the status of Verb Phrase.